Method for manufacturing silk fibroin molded body
Patent Information
- Application Number
- JP2023188199
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-11
- Filing Date
- 2023-11-02
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2039-11-28
AI Technical Summary
【0037】 本発明により、シルクフィブロイン成形体において、αヘリックス構造とβシート構造の割合を調整可能なシルクフィブロイン成形体の製造方法、さらに、αヘリックス構造に比べβシート構造を多く含むシルクフィブロインフィルムおよびその製造方法が提供される。
Smart Images

Figure 0007644390000003 
Figure 0007644390000001 
Figure 0007644390000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a silk fibroin molded article.
[0002] Silk fibroin molded articles, such as silk fibroin films, sheets, coatings, and fibers, exhibit high affinity with living organisms and have attracted attention as medical materials, such as cell scaffolding materials and cartilage regeneration materials in regenerative medicine. [Background technology]
[0003] Silk fibroin molded bodies such as silk fibroin films, sheets, coatings, or fibers can be obtained, for example, by dissolving silk fibroin, a protein produced by silkworm larvae in a solvent to prepare a silk fibroin solution, and then spreading the solution on a substrate and drying it. The Japanese Industrial Standards (JIS) packaging terminology standard defines a film as "a plastic membrane with a thickness of less than 250 μm" and a sheet as "a thin plastic plate with a thickness of 250 μm or more."
[0004] Silk fibroin, the raw material for silk fibroin molded products, is contained in silkworm cocoons or raw silk, and can be obtained by removing impurities such as sericin and other fats from the cocoons or raw silk.
[0005] Silk fibroin is known to be soluble in certain metal aqueous solutions, such as a mixture of calcium chloride and ethanol, formic acid, hexafluoroacetone, and 1,1,1,3,3,3-hexafluoro-2-propanol (HC(CF3)2OH, CAS number 920-66-1, hereafter sometimes referred to as HFIP).
[0006] Patent Document 1 describes that silk fibroin dissolves in an aqueous solution of a specific metal salt, such as calcium chloride, lithium bromide, lithium thiocyanate, and sodium thiocyanate, and describes that after dissolution, an aqueous silk fibroin solution can be obtained by removing the metal salt by dialysis.
[0007] Patent Documents 2 and 3 describe that silk fibroin is dissolved in an aqueous solution of a metal salt, and then dried to obtain silk fibroin, which is then soluble in HFIP.
[0008] A silk fibroin film or sheet can be obtained by spreading a silk fibroin aqueous solution or a silk fibroin HFIP solution on a substrate and then drying it. When the obtained film or sheet is used as a medical material, it is preferable that it is insoluble in water to prevent it from being immediately dissolved and lost in the body.
[0009] Patent Document 4 describes that the secondary structure of a silk fibroin molded body includes an α-helix structure and a β-sheet structure. Non-Patent Document 1 defines a β-sheet structure as "a protein secondary structure in which hydrogen bonds are formed between peptide bonds within or between molecules, resulting in an overall planar structure."
[0010] Patent Document 5 discloses a method for forming a water-insoluble fibroin molded body, including the steps of immersing the middle silk gland extracted from a silkworm in a 10% to 100% alcohol aqueous solution to fix it, removing impurities from the fixed middle silk gland to obtain fibroin protein, dissolving the fibroin protein in a wet state using a halogen-containing solvent to prepare a fibroin solution, and drying the fibroin solution to form a fibroin molded body, and HFIP is exemplified as the halogen-containing solvent. Patent Document 5 also discloses that the silk fibroin molded body (e.g., a film) produced from the above-mentioned silk fibroin aqueous solution is highly water-soluble and dissolves or loses strength when in contact with water.
[0011] In the examples of Patent Document 5, the aforementioned silk fibroin aqueous solution was freeze-dried to obtain a sponge-like dried product, which was then dissolved in HFIP and cast into a film, which was confirmed to be easily soluble in water.
[0012] In the examples of Patent Document 5, it has been confirmed that a film produced from the above-mentioned silk fibroin HFIP solution exhibits a spectrum derived from an α-helix structure in Fourier transform infrared spectroscopy, while a film produced from a solution obtained by dissolving the above-mentioned fibroin protein obtained from the middle silk gland in HFIP exhibits a spectrum derived from a crystalline β-sheet structure in Fourier transform infrared spectroscopy. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2001-163899 A [Patent Document 2] Special Publication No. 7-503288 [Patent Document 3] Special Publication No. 2006-504450 [Patent Document 4] JP 2004-68161 A [Patent Document 5] JP2017-149674A [Non-patent literature]
[0014] [Non-Patent Document 1] "Chemistry of Silk and Material Development" Yasushi Tamada, Chemistry and Education, Vol. 64, No. 9 (2016), pp. 456-459 Summary of the Invention [Problem to be solved by the invention]
[0015] Water-soluble silk fibroin molded bodies are generally not suitable as biomaterials, so they are subjected to an insolubilization treatment before use. As described in Patent Document 5, known insolubilization treatments include inducing crystallization by alcohol or by heat treatment.
[0016] However, Patent Document 5 describes that inducing crystallization by alcohol requires a drying step after the alcohol treatment, making the process complicated, and also describes that inducing crystallization by heat treatment requires high-temperature treatment at around 200°C, which leads to browning due to protein denaturation.It also describes that either treatment affects the higher-order structure of fibroin, resulting in a decrease in mechanical properties (causing brittleness).
[0017] Silk fibroin molded products are usually formed by spreading a silk fibroin solution on a substrate and drying it. In this case, if the obtained silk fibroin molded product contains more β-sheet structures than α-helix structures, insolubilization treatment is not necessary or can be simplified when used as a biomaterial.
[0018] The silk fibroin molded body has a certain ratio of α-helix structure and β-sheet structure. The conditions for insolubilization treatment depend on the ratio of α-helix structure to β-sheet structure in the silk fibroin molded body (hereinafter, sometimes referred to as αβ intensity ratio). In order to simplify the insolubilization treatment conditions by standardizing them or for quality control of the silk fibroin molded body, it is preferable that the silk fibroin molded body is produced with a certain ratio of α-helix structure to β-sheet structure.
[0019] The first object of the present invention is to provide a method for producing a silk fibroin molded body that allows adjustment of the ratio of α-helix structure and β-sheet structure in the silk fibroin molded body, and the second object is to provide a method for producing a silk fibroin film that contains more β-sheet structure than α-helix structure. [Means for solving the problem]
[0020] The secondary structure of proteins is known to include a right-handed alpha-helix structure in which amino and carboxyl groups are hydrogen-bonded, and a beta-sheet structure in which the NH of one main chain of adjacent peptide chains is hydrogen-bonded to the C=O of the adjacent main chain, forming a highly crystalline planar structure.
[0021] Patent Document 5 describes that dissolving silk fibroin in HFIP induces the secondary structure of the silk fibroin to an α-helix structure, and also describes that a film prepared from a solution in which silk fibroin is dissolved in HFIP contains a large amount of α-helix structure and is water-soluble.
[0022] In other words, it was conventionally believed that silk fibroin molded bodies obtained from a HFIP solution of silk fibroin contain more α-helical structures than crystalline β-sheet structures, and are water-soluble due to their low crystallinity.
[0023] As a result of extensive investigation, the present inventors have found that The present invention was arrived at by finding that the ratio of α-helix structure and β-sheet structure in a silk fibroin molded body can be adjusted by controlling the temperature and humidity during drying of a silk fibroin HFIP solution obtained by dissolving silkworm cocoons in a specific metal salt aqueous solution and then desalination, or by dissolving commercially available silk fibroin in HFIP, a fluorine-containing alcohol solvent, on a substrate, in which the silk fibroin HFIP solution is spread, and the ratio of α-helix structure and β-sheet structure in the silk fibroin molded body can be adjusted by controlling the temperature and humidity during drying. In the present invention, the casting method refers to a method of spreading a silk fibroin solution on a substrate and evaporating the solvent to obtain a silk fibroin molded body.
[0024] Furthermore, the inventors have found that a water-insoluble silk fibroin film rich in β-sheet structure can be produced by drying the film at room temperature (approximately 25°C) at a relative humidity of 40% or more and 95% or less, and then, if necessary, immersing the film in water, an alcohol having 1 to 3 carbon atoms, or an aqueous solution of the alcohol.
[0025] The present invention relates to the following <Invention 1> Includes. <Invention 1> A method for producing a silk fibroin molded body, comprising: a step of removing impurities from silkworm cocoons or raw silk to obtain silk fibroin to be used as a raw material; a step of dissolving the silk fibroin in a fluorine-containing solvent to prepare a silk fibroin solution; a first step of spreading the silk fibroin solution on a substrate; and a second step of drying the silk fibroin solution on the substrate while controlling the temperature and relative humidity (however, this does not include a method for forming a water-insoluble fibroin molded body, which includes a step of immersing a middle silk gland extracted from a silkworm in a 10% to 100% alcohol aqueous solution to fix it, a step of removing impurities from the fixed middle silk gland to obtain fibroin protein, a step of dissolving the fibroin protein in a wet state using a halogen-containing solvent to prepare a fibroin solution, and a step of drying the fibroin solution to form a fibroin molded body). The present invention relates to the above <Invention 1>, but other matters (eg, the following [Invention 1] to [Invention 11]) are also described below. [Invention 1] A method for producing a silk fibroin molded body, comprising: a first step of spreading a silk fibroin solution containing a fluorine-containing solvent on a substrate; and a second step of drying the silk fibroin solution on the substrate while controlling the temperature and relative humidity.
[0026] A preferred embodiment for "controlling temperature and relative humidity" in Invention 1 will be described in detail in the section "Controlling temperature and relative humidity" in the section "Mode for carrying out the invention."
[0027] [Invention 2] The method for producing a silk fibroin molded article according to Invention 1, wherein in the second step, the temperature is 10°C or higher and 120°C or lower, and the relative humidity is 5% or higher and 95% or lower.
[0028] [Invention 3] 3. The method for producing a silk fibroin molded article according to any one of Inventions 1 and 2, wherein the fluorine-containing solvent is a fluorine-containing alcohol.
[0029] [Invention 4] The method for producing a silk fibroin molded article according to Invention 3, wherein the fluorine-containing alcohol is 1,1,1,3,3,3-hexafluoro-2-propanol.
[0030] [Invention 5] 5. The method for producing a silk fibroin shaped article according to any one of Inventions 1 to 4, wherein the silk fibroin shaped article is a silk fibroin film or a silk fibroin sheet.
[0031] [Invention 6] 6. The method for producing a silk fibroin material according to any one of Inventions 1 to 5, further comprising a third step of immersing the silk fibroin material in water, an alcohol having 1 to 3 carbon atoms, or an aqueous solution of the alcohol.
[0032] [Invention 7] Infrared absorption spectrum at 1650cm -1 The intensity of the peak located near [abs(1650)] and 1620 cm -1 A silk fibroin film having an abs intensity ratio [abs(1650) / abs(1620) ] of 1 or less, which is the ratio of the intensities [abs(1620) ] of the peaks located near each other.
[0033] [Invention 8] Invention 7. A method for producing a silk fibroin film, comprising: a first step of spreading a silk fibroin solution containing a fluorine-containing solvent on a substrate; and a second step of drying the silk fibroin solution on the substrate at a temperature of 15°C or higher and 35°C or lower, and at a relative humidity of 40% or higher and 95% or lower.
[0034] [Invention 9] The method for producing a silk fibroin film according to Invention 8, wherein the fluorine-containing solvent is a fluorine-containing alcohol.
[0035] [Invention 10] The method for producing a silk fibroin film according to claim 9, wherein the fluorine-containing alcohol is 1,1,1,3,3,3-hexafluoro-2-propanol.
[0036] [Invention 11] 11. The method for producing a silk fibroin film according to any one of Inventions 8 to 10, further comprising a third step of immersing the silk fibroin film in water, an alcohol having 1 to 3 carbon atoms, or an aqueous solution of the alcohol. Effect of the Invention
[0037] The present invention provides a method for producing a silk fibroin molded body that allows adjustment of the ratio of α-helix structure to β-sheet structure, and further provides a silk fibroin film that contains more β-sheet structure than α-helix structure and a method for producing the same. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 is a graph showing the correlation between the relative humidity when a silk fibroin solution is dried on a substrate at 25°C and the abs intensity ratio of the peaks derived from the α-helix structure and the β-sheet structure in the Fourier transform infrared spectrum measurement of the resulting silk fibroin film, with the horizontal axis representing the relative humidity and the vertical axis representing the abs intensity ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The present invention will be described in more detail below, but the present invention is not limited to the following.
[0040] The method for producing a silk fibroin molded body of the present invention includes a first step of spreading a silk fibroin solution containing a fluorine-containing solvent on a substrate, and a second step of drying the silk fibroin solution on the substrate while controlling the temperature and relative humidity.
[0041] In addition, the silk fibroin film of the present invention has an infrared absorption spectrum of 1650 cm -1 The intensity of the peak due to the α-helical structure located near the center [abs(1650)] and the intensity at 1620 cm -1 The abs intensity ratio [abs(1650) / abs(1620) ] of the peak intensity [abs(1620) ] derived from the β-sheet structure located near the abs intensity ratio [abs(1650) / abs(1620) ] can be made equal to or less than 1. In other words, a silk fibroin film containing more β-sheet structures than α-helix structures can be obtained.
[0042] In this specification, the infrared absorption spectrum at 1650 cm -1Nearby is 1650cm -1 Centered at ±10cm -1 This refers to the range of 1650 cm -1 The nearby peaks are 1650cm -1 Centered at ±10cm -1 This means the maximum peak within the range.
[0043] In this specification, the infrared absorption spectrum of 1620 cm -1 Nearby is 1620cm -1 Centered at ±10cm -1 This refers to the range of 1620 cm -1 The nearby peaks are 1620cm -1 Centered at ±10cm -1 This means the maximum peak within the range.
[0044] The method for producing a silk fibroin molded article of the present invention may be carried out by reducing or increasing the operating environment from atmospheric pressure, but can be carried out at atmospheric pressure (approximately 101.325 kPa standard pressure).
[0045] 1. Silk fibroin In the method for producing a silk fibroin molded article and the silk fibroin film of the present invention, silk fibroin used as a raw material can be obtained by removing impurities from silkworm cocoons or raw silk. The cocoon threads spit out by silkworm larvae consist of fibroin filaments and the gelatinous sericin that covers the filaments, and the cocoon balls are created by bonding the fibroin filaments with sericin. The fibroin content in the cocoon ball is 70 to 80% by mass, the sericin content is 20 to 30% by mass, and other impurities such as small amounts of fat are also included. The raw silk is thread extracted from the cocoon after the cocoon ball is immersed in hot water to dissolve it, and contains impurities.
[0046] Silkworm species that produce silk fibroin used in the method for producing silk fibroin molded articles or silk fibroin film of the present invention are not particularly limited. For example, silkworm species that are included in the order Lepidoptera include Saturniidae, Bombycidae, Ophiopogonidae, Lasiocampidae, Lymantriidae, Arctiidae, Tufted moth, Noctuidae, Pyrrhodontidae, Agrotiidae, Plutellaceae, Zygaenidae, Parasitidae, Limacodidae, Pyralidae, Papilionidae, Sycamoreidae, Papilionidae, or genetically modified varieties thereof. Since they are easily available in Japan, Saturniidae, Bombycidae, or genetically modified varieties thereof are preferred, and Bombycidae and genetically modified varieties thereof are particularly preferred.
[0047] In the method for producing a silk fibroin molded article of the present invention, silk fibroin obtained through, for example, degumming can be used. Degumming is a process for removing the above-mentioned impurities from cocoons. For example, the above-mentioned impurities can be removed by contacting the cocoons or raw silk with an alkaline solution such as soap solution, lye or soda solution. Silk fibroin that is commercially available as silk thread, silk fabric, health food, etc. may also be used.
[0048] In addition, silk fibroin directly collected from the silk glands of silkworm larvae can also be used. When using silk glands, silk fibroin selected from the silk glands as they are after being harvested from silkworm larvae may be used, but fibroin contained in silk glands obtained by fixing the harvested silk glands in methanol, ethanol, 1-propanol, 2-propanol, or a mixed aqueous solution of these at a concentration of 10 to less than 99% by volume may also be used.
[0049] The molecular weight (Mw) of silk fibroin used in the method for producing a silk fibroin molded article of the present invention is not particularly limited. Although it depends on the type of alkaline solution used in scouring the cocoons or raw silk and the scouring conditions, the Mw of silk fibroin is usually 50,000 to 370,000. The literature value of silk fibroin produced from the silk gland of domesticated silkworms is 370,000 (non-patent literature: Tashiro Yutaka and Otsuki Eiichi, Journal of Cell Biology, Vol. 46, P1 (1970), non-patent literature: Prog. Polym. Sci. 2007; 32 (8-9): 991-1007).
[0050] In the method for producing a silk fibroin molded article of the present invention, silk fibroin is dissolved in a fluorine-containing solvent to prepare a silk fibroin solution, and the solution is then spread on a substrate and dried to obtain a molded article such as a silk fibroin film, sheet, coating, or fiber.
[0051] 2. Silk fibroin solution 2-1. Fluorine-containing solvents The fluorine-containing solvent may be any solvent capable of dissolving silk fibroin, and may preferably be a fluorine-containing alcohol, hexafluoroacetone (HFA) or a hydrate thereof, and more preferably be a fluorine-containing alcohol. Specific examples of the fluorine-containing alcohol include, but are not limited to, HFIP, 2,2,2-trifluoroethanol, and perfluoroalcohols having 1 to 3 carbon atoms, and preferably HFIP. The fluorine-containing solvent may be used alone or in combination. The fluorine-containing solvent may be used in combination with one or more other solvents. The other solvent may be any solvent that does not cause deterioration of silk fibroin or a decrease in molecular weight and does not hinder dissolution. Examples of such solvents include water, N-methylmorpholine N-oxide, methanol, acetone, tetrahydrofuran, N,N-dimethylacetamide, toluene, or dichloromethane. When obtaining a silk fibroin solution, these solvents may be used within a range of 20 or less, preferably 15 or less, and more preferably 10 or less, expressed as a relative ratio with respect to the mass of the fluorine-containing solvent being 100.
[0052] 2-2. Concentration of silk fibroin solution The concentration of silk fibroin in the silk fibroin solution used in the method for producing a silk fibroin molded article of the present invention is 0.01% by mass or more and 50% by mass or less, based on the total amount of the silk fibroin solution. It is preferably 0.1% by mass or more and 40% by mass or less, and particularly preferably 1% by mass or more and 25% by mass or less. If the concentration is 0.01% by mass or more, the productivity of the molded article is high, which is preferable. If it is 50% by mass or less, the viscosity of the silk fibroin solution is easy to handle and easy to mold.
[0053] 2-3. Melting temperature of silk fibroin The temperature at which silk fibroin is dissolved in the fluorine-containing solvent is not particularly limited. It is sufficient that the fluorine-containing solvent does not solidify or evaporate. When a closed pressure vessel (autoclave) is not used, the temperature is, for example, 0°C or higher and 120°C or lower. More preferably, it is 10°C or higher and 80°C or lower, and particularly preferably, it is 15°C or higher and 60°C or lower. When a closed pressure vessel is used, the temperature is, for example, 0°C or higher and 200°C or lower. More preferably, it is 10°C or higher and 160°C or lower, and particularly preferably, it is 15°C or higher and 140°C or lower.
[0054] 2-4. Silk fibroin dissolution time The time for dissolving silk fibroin in the fluorine-containing solvent is not particularly limited. The dissolution time depends on the temperature, but is, for example, 0.5 hours or more and 168 hours or less. More preferably, it is 0.75 hours or more and 96 hours or less, and particularly preferably, it is 1 hour or more and 72 hours or less.
[0055] 3. Manufacturing method of silk fibroin molded body The method for producing a silk fibroin molded body of the present invention includes a first step of spreading a silk fibroin solution containing a fluorine-containing solvent on a substrate, and a second step of drying the silk fibroin solution on the substrate while controlling the temperature and relative humidity.
[0056] 3-1. First process (development process) The first step is a step of spreading the silk fibroin solution on a substrate (hereinafter, sometimes referred to as a spreading step).
[0057] There is no particular limitation on the method for spreading the silk fibroin solution on the substrate.
[0058] [Base] In the method for producing a silk fibroin molded product of the present invention, the substrate on which the silk fibroin solution is spread may be any substrate having a flat or curved surface that is not affected by the silk fibroin solution and can spread the silk fibroin solution uniformly. The substrate may be a flat plate, a frame, a petri dish, or a cylinder, depending on the shape of the desired molded product, and may be made of resin, metal, glass, or ceramic.
[0059] Expand In the method for producing a silk fibroin molded article of the present invention, the spreading refers to the act of pouring a fluid into a mold and arranging the fluid into a desired shape of the molded article in order to obtain a desired shape of the molded article, for example, pouring a silk fibroin solution into a cylindrical mold, such as a petri dish. It also includes using a syringe or the like to extrude a fluid into a fibrous form.
[0060] [Expansion conditions] In the spreading step, the temperature at which the silk fibroin solution is spread on the substrate is 10° C. or higher and 120° C. or lower, depending on the boiling point of the solvent used, preferably 15° C. or higher and 80° C. or lower, and more preferably 20° C. or higher and 40° C. or lower.
[0061] When the solvent is HFIP, since the boiling point of HFIP is 58.6°C, the temperature at which the silk fibroin solution is spread on the substrate is 58.6°C or lower, and preferably 20°C or higher and 40°C or lower.
[0062] The second step is a step of drying the silk fibroin solution on or after spreading it on a substrate (hereinafter, sometimes referred to as a drying step). The drying step removes the fluorine-containing solvent from the silk fibroin solution, thereby producing a silk fibroin molded product such as a silk fibroin film, sheet, coating, or fiber.
[0063] "Drying" refers to removing liquid from a target object by applying heat or the like to dry it, or to being in a dry state; however, in this specification, "drying" mainly refers to removing the fluorinated solvent to dry it.
[0064] The drying conditions for the silk fibroin solution in the drying process are described below.
[0065] [temperature] In the drying step, the environmental temperature when drying the silk fibroin solution spread on the substrate or on the substrate is 10°C or higher and 120°C or lower, depending on the boiling point of the solvent used. It is preferably 15°C or higher and 40°C or lower, and more preferably 15°C or higher and 35°C or lower. A temperature of 10°C or higher is preferable because it does not require an excessively long time for drying. A temperature of 120°C or lower is preferable because there is no risk of the silk fibroin being altered by heat.
[0066] [Relative Humidity] In the drying step, the relative humidity during drying of the silk fibroin solution spread on the substrate is 5% or more and 95% or less. After spreading the silk fibroin solution on the substrate, the temperature and relative humidity are controlled, and the silk fibroin solution is dried on the substrate, whereby a silk fibroin molded product having a desired abs strength ratio can be obtained.
[0067] Silk fibroin molded products produced under the conditions of the examples of the present invention can be dried in an environment of a temperature of 15° C. or higher and 35° C. or lower and a relative humidity of 40% or higher and 95% or lower, as shown in FIG. 1, to obtain a silk fibroin film that is insoluble in water and has an abs intensity ratio of 1 or less. In addition, by drying at a temperature of 15° C. or higher and 35° C. or lower and a relative humidity of less than 40%, a water-soluble silk fibroin film with an abs intensity ratio exceeding 1 can be obtained. From this, it can be seen that if the silk fibroin solution is dried on a substrate while controlling the temperature and relative humidity in the second step, a silk fibroin molded product having a desired ratio of α-helix structure and β-sheet structure can be obtained.
[0068] [Temperature and relative humidity control] In order to obtain a silk fibroin molded product having a desired abs strength ratio, it is preferable to set the temperature to a desired temperature (X°C) within a range of 10°C to 120°C, preferably 15°C to 40°C, more preferably 15°C to 35°C, and control the temperature fluctuation from (X°C) to within ±20°C, preferably within ±10°C, and particularly preferably within ±5°C, and set the relative humidity to a desired relative humidity (Y%) within a range of 5% to 95%, and control the fluctuation to within ±20%, preferably within ±10%, and particularly preferably within ±5%, during the drying process, when the amount of evaporation of the solvent contained in the solution is 10% to 100% of the theoretical evaporation amount defined below. By controlling the temperature and relative humidity, the silk fibroin molded product obtained in the second process has a constant abs strength ratio.
[0069] In the present invention, the abs intensity ratio is the ratio of the abs intensity at 1650 cm -1 The intensity of the peak located near [abs(1650)] and 1620 cm -1 This refers to the abs intensity ratio [abs(1650) / abs(1620)] of the intensity of the peak located near the center [abs(1620)]. The lower this value, the greater the ratio of β-sheet structures to α-helix structures in the silk fibroin molded product, and the less soluble the silk fibroin molded product in water will be.
[0070] <Theoretical evaporation amount> The theoretical evaporation amount was calculated according to the following formula. Theoretical evaporation amount (g) = weight of casting solution (g) × (100 - silk fibroin concentration (%)) / 100
[0071] [time] In the drying step, the time for drying the silk fibroin solution spread on or in the substrate is not particularly limited. Although it depends on the temperature and relative humidity of the environment, and the concentration and amount of the silk fibroin solution used, it is preferably 0.1 seconds or more and 92 hours or less, more preferably 1 second or more and 72 hours or less. If the drying time is shorter than 1 second, the evaporation of the solvent may be insufficient. If the dissolution time is longer than 72 hours, the productivity is low and it is not practical. It is preferable to end the drying after confirming that there is no change in weight when the appearance of the obtained silk fibroin molded body and when the molded body is weighed (for example, when the molded body is placed on a balance together with the substrate and weighed).
[0072] [Drying] In the method for producing a silk fibroin molded product of the present invention, the environment in which the silk fibroin solution spread on the substrate is dried is not particularly limited as long as the environment can maintain a constant temperature and relative humidity. A normal environment such as a fume hood in a laboratory, a desiccator equipped with a desiccant, or an environmental tester may be used.
[0073] 4. Silk fibroin molded body The shape of the silk fibroin molded article obtained by the method for producing a silk fibroin molded article of the present invention is not limited.
[0074] [Film thickness] When the molded product is a silk fibroin film, the film thickness can be controlled to a desired value by appropriately adjusting the amount and concentration of the silk fibroin solution. Since the film thickness is easily controlled, the film thickness is preferably 1 μm or more and less than 250 μm.
[0075] When the molded product is a silk fibroin sheet, the thickness can be controlled to a desired value by appropriately adjusting the amount and concentration of the silk fibroin solution. Since the thickness can be easily controlled, the thickness is preferably 250 μm or more and less than 2 cm.
[0076] [Fiber diameter] When the molded product is a silk fibroin fiber, the amount and concentration of the silk fibroin solution can be appropriately adjusted to control the fiber diameter to a desired value, for example, 50 nm or more and 1 mm or less, preferably 100 nm or more and 500 μm or less, and particularly preferably 500 nm or more and 250 μm or less.
[0077] [Secondary structure of silk fibroin molded body] According to the method for producing a silk fibroin molded article of the present invention, a silk fibroin molded article such as a film, sheet, coating, or fiber can be obtained.
[0078] 5. Washing of silk fibroin molded bodies The silk fibroin molded body obtained by the method for producing a silk fibroin molded body of the present invention may be washed as necessary. Most of the solvent used in molding is removed during drying, but washing can further reduce the content of the solvent. In the case of an insoluble silk fibroin molded body (abs intensity ratio is 2.3 or less, preferably 1.7 or less, particularly preferably 1.0 or less), the obtained film can be immersed in water, methanol, ethanol, 1-propanol, isopropanol, or a mixed solution thereof for washing. There is no particular limit to the temperature of the solvent used for washing, but it is preferably 5°C or more and 100°C or less, more preferably 10°C or more and 60°C or less. There is also no particular limit to the immersion time, but it is preferably 10 seconds or more and 24 hours or less, more preferably 30 seconds or more and 2 hours or less. After immersion, it can also be dried by ordinary means such as air drying or heating (e.g., hot pressing) as necessary. In addition, when the abs intensity ratio of the silk fibroin molded body exceeds 1.0, the molded body is easily dissolved in water, so water cannot be used for the above washing, but methanol, ethanol, 1-propanol, isopropanol, or a mixed solution thereof can be used. There is no particular limitation on the concentration of the above mixed solution, as long as they are compatible with each other and do not dissolve the molded body. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In addition, Examples 6, 7, 9 to 12, 14, 15, 17 and 18 should be read as Reference Examples 6, 7, 9 to 12, 14, 15, 17 and 18, respectively.
[0080] [Preparation of silk fibroin (refining of cocoons)] In a 500mL glass separable flask, 500mL of sodium carbonate aqueous solution prepared to a concentration of 0.2% by mass and 10.0g of cocoon balls (variety: Kinshu x Kanewa) were placed and heated to 100°C and boiled. After boiling for 2 hours, the mixture was left to stand and cooled to 40°C, and the contents were suction filtered with a filter to remove the cocoon balls. The cocoon balls were then returned to the separable flask, 500mL of ion-exchanged water was added to the flask, and the mixture was heated to 100°C, boiled, and washed. After boiling for 30 minutes, the mixture was cooled to 40°C and suction filtered. This washing operation was repeated twice, and the cocoon balls were placed in a vacuum dryer and dried under reduced pressure at 60°C and 10hPa for 6 hours to obtain 6.90g of silk fibroin. The weight-average molecular weight (Mw) of the obtained silk fibroin was measured by gel permeation chromatography (hereinafter sometimes referred to as GPC) and found to be 160,000.
[0081] [Preparation of silk fibroin sponge] The silk fibroin sponge was prepared by the following Silk Fibroin Sponge Preparation (1) or Silk Fibroin Sponge Preparation (2).
[0082] <Preparation of silk fibroin sponge (1)> 5.00 g of silk fibroin obtained in the above-mentioned [Preparation of silk fibroin] was placed in a 100 mL glass flask equipped with a Dimroth type reflux condenser, and 50 mL of calcium chloride / ethanol aqueous solution (calcium chloride:ethanol:water = 1:2:8 (molar ratio)) was added. The bottom of the flask was then immersed in an oil bath at 60° C. for 1 hour to dissolve the silk fibroin, and an aqueous silk fibroin solution was obtained. The aqueous silk fibroin solution was then filtered, and the filtrate was collected.
[0083] The filtrate was added to a dialysis tube (Spectrum Laboratories, USA, regenerated cellulose membrane, product name: Spectra / por4, molecular weight fraction 12-14 kDa), and dialysis was performed using ion-exchanged water as the dialysis buffer to remove calcium chloride and ethanol. The dialysis buffer was replaced every 8 hours for a total of 12 times. The aqueous solution in the dialysis tube was freeze-dried to obtain a porous silk fibroin sponge.
[0084] The yield of silk fibroin sponge was 4.36 g, and the yield was 87.2%. The weight average molecular weight (Mw) was measured by GPC and found to be 160,000, which was equivalent to the Mw of the raw silk fibroin obtained in [Preparation of silk fibroin].
[0085] <Preparation of silk fibroin sponge (2)> In a 100 mL glass flask equipped with a Dimroth type reflux condenser, 1.00 g of cocoons (variety: Kinshu x Kanewa) cut into 10 mm x 10 mm pieces were collected, and 50 mL of calcium chloride / ethanol aqueous solution (calcium chloride:ethanol:water = 1:2:8 (molar ratio)) was added. Next, the bottom of the flask was immersed in an oil bath at 90 °C and heated for 3 hours to dissolve the cocoons and obtain an aqueous solution of cocoon proteins. Next, the aqueous solution of cocoon proteins was filtered, and the filtrate was collected. This filtrate was added to a dialysis tube (Spectrum Laboratories, USA, regenerated cellulose membrane, product name: Spectra / Por4, molecular weight fraction 12-14 kDa), and dialysis was performed using ion-exchanged water as the dialysis buffer to remove calcium chloride and ethanol. The dialysis buffer was replaced every 8 hours for a total of 12 times. The aqueous solution in the dialysis tube was freeze-dried to obtain a porous silk fibroin sponge. The yield of the silk fibroin sponge was 0.52 g, which was a yield of 51.9%. The weight average molecular weight (Mw) was measured by GPC and found to be 390,000.
[0086] [Measurement of protein weight-average molecular weight (Mw) by GPC] In measuring the Mw of silk fibroin, a GPC apparatus manufactured by Tosoh Corporation (product name: HLC-8320GPC) was used, and two columns manufactured by Tosoh Corporation (product name: TSK gel Super HM-H) were used in combination. The column contained 5×10 -3 HFIP containing a molar concentration of sodium trifluoroacetate was run through the tube. A calibration curve was created using polymethyl methacrylate as a standard substance, and the weight-average molecular weight of silk fibroin was calculated.
[0087] The GPC measurement sample was prepared by weighing out 10 mg of silk fibroin into a test tube containing 1 mL of hexafluoroacetone trihydrate and dissolving it at room temperature (25°C). 5 μL of the solution was then taken with a microsyringe and added to 2 mL of the above eluent to prepare the GPC measurement sample.
[0088] [Preparation of silk fibroin HFIP solution] The silk fibroin HFIP solutions were prepared by the following Preparation of Silk Fibroin HFIP Solution (1), Preparation of Silk Fibroin HFIP Solution (2), or Preparation of Silk Fibroin HFIP Solution (3).
[0089] <Preparation of silk fibroin HFIP solution (1)> In a 100 mL stainless steel pressure vessel equipped with a thermometer and a stirrer, 0.2 g of silk fibroin obtained in the above-mentioned [Preparation of silk fibroin] was weighed out at room temperature (25 ° C), and 19.8 g of HFIP was taken so that the concentration of silk fibroin was 1 mass %. Next, the inside of the pressure vessel was heated to 110 ° C, and the mixture was stirred for 2 hours to dissolve the silk fibroin. 10.0 g of HFIP was distilled off under reduced pressure using an evaporator from the obtained silk fibroin HFIP solution, to obtain 10.0 g of silk fibroin HFIP solution (A) with a concentration of 2 mass %.
[0090] <Preparation of silk fibroin HFIP solution (2)> In a glass eggplant-shaped flask equipped with a stirrer, 0.2 g of the silk fibroin sponge (Mw: 160,000) obtained in the above-mentioned <Preparation of silk fibroin sponge (1)> was weighed out, and then 9.8 g of HFIP was added. The mixture was then stirred at room temperature (25°C) for 6 hours to dissolve the silk fibroin sponge, and 10.0 g of a 2% by mass silk fibroin HFIP solution (B) was obtained.
[0091] <Preparation of silk fibroin HFIP solution (3)> In a glass eggplant-shaped flask equipped with a stirrer, 0.2 g of the silk fibroin sponge (Mw: 390,000) obtained in the above-mentioned <Preparation of silk fibroin sponge (2)> was weighed out, and then 19.8 g of HFIP was added. The mixture was then stirred at room temperature (25°C) for 24 hours to dissolve the silk fibroin sponge, and the insoluble matter was removed by filtration. 10.0 g of HFIP was removed under reduced pressure from the obtained silk fibroin HFIP solution using an evaporator, to obtain 10.0 g of a silk fibroin HFIP solution (C) with a concentration of 2% by mass.
[0092] [Thickness measurement of silk fibroin film] The thickness of the silk fibroin film was measured. A micrometer manufactured by Mitutoyo Corporation, product name: MDC-25MX, was used for the measurement. Measurements were taken at five arbitrary points including the center of the film, and the average value was taken as the film thickness.
[0093] Example 1 10 mL of the 2% by mass silk fibroin HFIP solution (A) obtained in the above <Preparation of silk fibroin HFIP solution (1)> was spread on a sterile polystyrene petri dish (88 mm diameter) and covered with a lid. The dish was then placed in a desiccator adjusted to a temperature of 25°C and a relative humidity of 10%, and the lid was removed and the dish was dried for 48 hours to obtain a silk fibroin film. During drying, the temperature was controlled at 25±5°C and the relative humidity was controlled at 10±5%. The thickness of the silk fibroin film was 50 μm.
[0094] Examples 2 to 5 Except for changing the relative humidity to 30% (Example 2), 40% (Example 3), 50% (Example 4), and 70% (Example 5), the temperature was controlled within ±5°C and the relative humidity was controlled within ±5% in the same manner as in Example 1 to obtain silk fibroin films. The thickness of each film was 50 μm.
[0095] Example 6 10 mL of the 2% by mass silk fibroin HFIP solution (B) obtained in the above-mentioned <Preparation of silk fibroin HFIP solution (2)> was spread on the sterilized polystyrene petri dish and covered with a lid. The dish was then placed in a desiccator adjusted to a temperature of 25°C and a relative humidity of 70%, and the lid was removed and the dish was dried for 48 hours to obtain a silk fibroin film. During drying, the temperature was controlled at 25±5°C and the relative humidity at 70±5%. The thickness of the silk fibroin film was 50 μm.
[0096] Example 7 10 mL of the 2% by mass silk fibroin HFIP solution (C) obtained in the above-mentioned <Preparation of silk fibroin HFIP solution (3)> was spread on the sterilized polystyrene petri dish and covered with a lid. Next, the dish was placed in a desiccator adjusted to a temperature of 25°C and a relative humidity of 70%, and the lid was removed and the dish was dried for 48 hours to obtain a silk fibroin film. During drying, the temperature was controlled at 25±5°C and the relative humidity was controlled at 70±5%. The thickness of the silk fibroin film was 50 μm.
[0097] Example 8 Except for changing the relative humidity to 14%, the temperature was controlled within ±5° C. and the relative humidity was controlled within ±5%, similarly to Example 1, to obtain a silk fibroin film. The film thickness was 50 μm.
[0098] Examples 9-10 Except for changing the relative humidity to 14% (Example 9) and 50% (Example 10), the temperature was controlled within ±5°C and the relative humidity was controlled within ±5% in the same manner as in Example 6 to obtain silk fibroin films. The thickness of each film was 50 μm.
[0099] Examples 11-12 Except for changing the relative humidity to 14% (Example 11) and 50% (Example 12), the temperature was controlled within ±5°C and the relative humidity was controlled within ±5% in the same manner as in Example 7 to obtain silk fibroin films. The thickness of each film was 50 μm.
[0100] Comparative Example 1 In a 100 mL glass flask equipped with a Dimroth type reflux condenser, 1.00 g of silk fibroin obtained in the above-mentioned [Preparation of silk fibroin] was collected, and 50 mL of calcium chloride / ethanol aqueous solution (calcium chloride:ethanol:water = 1:2:8 (molar ratio)) was added. Next, the bottom of the flask was immersed in an oil bath at 90 °C and heated for 3 hours to dissolve the cocoons and obtain an aqueous solution of cocoon proteins. Next, the aqueous solution of cocoon proteins was filtered, and the filtrate was collected. This filtrate was added to a dialysis tube (Spectrum Laboratories, USA, regenerated cellulose membrane, product name: Spectra / Por4, molecular weight fraction 12-14 kDa), and dialysis was performed using ion-exchanged water as the dialysis buffer to remove calcium chloride and ethanol. The dialysis buffer was replaced every 8 hours for a total of 12 times. 10 mL of the aqueous solution of silk fibroin in this dialysis tube was spread in a polystyrene petri dish and covered with a lid. Next, the silk fibroin film was obtained by placing it in a desiccator adjusted to a temperature of 25°C and a relative humidity of 15%, removing the lid and drying it for 48 hours. During drying, the temperature was controlled to 25±5°C and the relative humidity to 15±5%. The silk fibroin film obtained had a thickness of 50 μm.
[0101] Comparative Example 2 Except for changing the relative humidity to 50%, the temperature was controlled within ±5°C and the relative humidity was controlled within ±5% to obtain a silk fibroin film in the same manner as in Comparative Example 1. The thickness of the silk fibroin film was 50 μm.
[0102] Comparative Example 3 Except for changing the relative humidity to 70%, the temperature was controlled within ±5°C and the relative humidity was controlled within ±5% in the same manner as in Comparative Example 1 to obtain a silk fibroin film. The film thickness of the silk fibroin film was 50 μm.
[0103] [Evaluation of Insolubility in Water] The silk fibroin films obtained in Examples 1 to 12 were immersed in water at room temperature for 1 hour, followed by visual observation and evaluation according to the following criteria. A: No change was observed in the appearance. B: Some defects were observed in the appearance. C: Completely dissolved.
[0104] [Confirmation of Higher-order Structure by Fourier Transform Infrared (FTIR) Spectrum Measurement] The IR spectrum of the obtained silk fibroin film was measured. As the IR spectrum measuring device, NicoletiS5 manufactured by Thermo Fisher Scientific was used.
[0105] <abs intensity ratio> In the FTIR spectrum measurement of the silk fibroin film, the intensity of the peak derived from the α-helix structure observed near 1650 cm -1 [abs(1650)], and the intensity of the peak derived from the β-sheet structure observed near 1620 cm -1 [abs(1620)], the abs intensity ratio [abs(1650) / abs(1620)] was calculated (Regarding the wave numbers of the peaks derived from each higher-order structure, refer to Non-Patent Document Taiyo Yoshioka, Tamako Hata, Katsura Kojima, Yasumoto Nakazawa, and Tsunenori Kameda, Biomater. Sci. Eng., Vol.3, P3207-3214 (2017)).
[0106] Table 1 shows the values of the abs intensity ratio [abs(1650) / abs(1620)] and the evaluation of insolubility in water of the films obtained in Examples 1 to 12 and Comparative Examples 1 to 3.
[0107] FIG. 1 shows a graph plotting the relative humidity on the horizontal axis and the abs intensity ratio on the vertical axis for the films obtained in Examples 1 to 12 and Comparative Examples 1 to 3.
[0108] [Table 1]
[0109] As shown in Table 1, Example 1 (relative humidity 10%) and Example 2 (relative humidity 30%) In Example 8 (relative humidity 14%), the abs intensity ratios of silk fibroin were 3.22, 1.12, and 2.21, respectively, and the intensity of the [abs(1650)] peak derived from the α-helix structure was large, indicating solubility in water.
[0110] On the other hand, the silk fibroin film dried in Example 3 (relative humidity 40%) had an abs intensity ratio of 0.73 and a large peak intensity of [abs(1620) ] derived from the β-sheet structure, indicating that the obtained silk fibroin film was insoluble in water.
[0111] The abs intensity ratios of the silk fibroin films obtained in Example 4 (relative humidity 50%) and Example 5 (relative humidity 70%) were 0.66 and 0.60, respectively, which were lower than the abs intensity ratio of 0.73 in Example 3 at a relative humidity of 40%. In other words, the higher the relative humidity, the higher the peak intensity of [abs(1620)] derived from the β-sheet structure. The lower the relative humidity, the higher the intensity of the [abs(1650)] peak due to the α-helical structure. In other words, the secondary structure in silk fibroin could be controlled by the temperature and relative humidity during drying.
[0112] Moreover, in Examples 6, 7, and 9 to 12, the abs intensity ratios of the silk fibroin films were equivalent to those in Examples 1 to 5 and 8 at the same relative humidity.
[0113] On the other hand, in Comparative Examples 1 to 3, the molded products obtained from the aqueous solutions had a constant abs intensity ratio regardless of the difference in relative humidity, as shown by the abs intensity ratio in Table 1, and it was not possible to adjust the abs intensity ratio compared to the case where the fluorine-containing solvent of the Examples was used.
[0114] Example 13 The silk fibroin film obtained in Example 5 was immersed in ion-exchanged water for 1 hour, and then dried at room temperature to obtain a washed silk fibroin film.
[0115] Example 14 The silk fibroin film obtained in Example 6 was immersed in ion-exchanged water for 1 hour, and then dried at room temperature to obtain a washed silk fibroin film.
[0116] Example 15 The silk fibroin film obtained in Example 7 was immersed in ion-exchanged water for 1 hour, dried at room temperature, and washed to obtain a silk fibroin film.
[0117] Example 16 The silk fibroin film obtained in Example 8 was immersed in ethanol for 1 hour, and then dried at room temperature to obtain a washed silk fibroin film.
[0118] Example 17 The silk fibroin film obtained in Example 9 was immersed in ethanol for 1 hour and dried at room temperature to obtain a washed silk fibroin film.
[0119] Example 18 The silk fibroin film obtained in Example 11 was immersed in ethanol for 1 hour, and then dried at room temperature to obtain a washed silk fibroin film.
[0120] Comparative Example 4 The silk fibroin film obtained in Comparative Example 1 was immersed in ethanol for 1 hour, dried at room temperature, and washed to obtain a silk fibroin film. The thickness of the silk fibroin film was 50 μm.
[0121] Comparative Example 5 The silk fibroin film obtained in Comparative Example 2 was immersed in ethanol for 1 hour, dried at room temperature, and washed to obtain a silk fibroin film. The thickness of the silk fibroin film was 50 μm.
[0122] Comparative Example 6 The silk fibroin film obtained in Comparative Example 3 was immersed in ethanol for 1 hour, dried at room temperature, and washed to obtain a silk fibroin film. The thickness of the silk fibroin film was 50 μm.
[0123] [Residual solvent evaluation] The residual solvent (HFIP) in the obtained silk fibroin film was quantified. Combustion ion chromatography was used to quantify the solvent. Sodium fluoride was used for the calibration curve, and the amount of residual solvent in the silk fibroin film was calculated from the amount of fluorine ions in the calibration curve using formula I. HFIP (ppm) = (fluorine ion concentration / 6) × (168 / (19 × 6)) Formula I Combustion equipment: AQF-2100H, manufactured by Mitsubishi Chemical Analytech Co., Ltd. Ion chromatograph: DIONEX ICS5000+, Thermo Fisher Scientific Column: AG11-HC (4 x 50 mm) / AS11-HC (4 x 250 mm), Thermo Fisher Scientific ·Eluent; KOH aqueous solution
[0124] [Evaluation of film mechanical properties through tensile tests] The mechanical properties of the obtained silk fibroin film were measured using an Autograph manufactured by Shimadzu Corporation, product name: AG-IS, as the mechanical property measuring device.
[0125] The test pieces were cut into strips with a length of 40 mm and a width of 2 mm. The test conditions were a chuck distance of 20 mm and a pulling speed of 10 mm / min. The thickness of the films used in the test was 50 μm.
[0126] Table 2 shows the measurement results of the abs strength ratio, residual solvent (HFIP), elastic modulus in the tensile test, stress at break, and strain at break of the silk fibroin films obtained in Examples 5 to 7, Examples 13 to 18, and Comparative Examples 1 to 3.
[0127] [Table 2]
[0128] As shown in Table 2, the silk fibroin films obtained in Examples 5 to 7 and Examples 13 to 18 had the same or higher breaking stress and breaking strain as the silk fibroin films obtained in Comparative Examples 4 to 6. In addition, among the obtained Examples, when the film was immersed in ion-exchanged water or ethanol and washed, the amount of fluorine solvent in the molded product was reduced. The film showed the same mechanical strength as the film that was not washed, and molded products could be produced without a significant decrease in mechanical properties.
[0129] As shown in Tables 1 and 2, by using the method for producing a silk fibroin molded product of the present invention, the ratio of α-helix structure and β-sheet structure of the silk fibroin molded product dried by controlling the temperature and relative humidity from a silk fibroin solution containing a fluorinated solvent can be adjusted to a desired value, and further, silk fibroin molded products containing more β-sheet structure than α-helix structure can be obtained.
Claims
[Claim 1] A process for removing impurities from silkworm cocoons or raw silk to obtain silk fibroin to be used as a raw material; A step of dissolving the silk fibroin in a fluorine-containing solvent to obtain a silk fibroin solution; A method for producing a silk fibroin molded body, comprising: a first step of spreading the silk fibroin solution on a substrate; and a second step of drying the silk fibroin solution on the substrate while controlling temperature and relative humidity (excluding a method for forming a water-insoluble fibroin molded body, comprising: a step of immersing a middle silk gland extracted from a silkworm in a 10% to 100% alcohol aqueous solution to fix it; a step of removing impurities from the fixed middle silk gland to obtain fibroin protein; a step of dissolving the fibroin protein in a wet state using a halogen-containing solvent to prepare a fibroin solution; and a step of drying the fibroin solution to form a fibroin molded body).
Citation Information
Patent Citations
A fiber-spinnable solution of silkworm fibroin
JP1995503288A
Method for producing functional silk fibroin and its use
JP2001163899A
Method for producing fiber, film and nonwoven fabric of silk and silky material and fiber, film or nonwoven fabric produced by the method
JP2004068161A
JP2006‐504450A
Method for removing organic solvent
JP2013139487A